2018
DOI: 10.1177/0963721418787475
|View full text |Cite
|
Sign up to set email alerts
|

Getting a Grip on Cognitive Flexibility

Abstract: Cognitive flexibility refers to the ability to quickly reconfigure our mind, like when we switch between different tasks. This review highlights recent evidence showing that cognitive flexibility can be conditioned by simple incentives typically known to drive lower-level learning, such as stimulus-response associations. Cognitive flexibility can also become associated with, and triggered by, bottom-up contextual cues in our environment, including subliminal cues. Therefore, we suggest that the control functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
129
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 41 publications
13
129
0
1
Order By: Relevance
“…These findings are consistent with a number of previous observations indicating that abstract goals or cognitive control functions can bind to contextual features in our environment, allowing for the recruitment of these functions upon contextual demand (Abrahamse et al, 2016). A more recent line of studies also extended this observation to the domain of "cognitive flexibility"the ability to quickly reconfigure our task sets to meet new goals (for a review, see Braem & Egner, 2018). For example, in a design where specific task items were associated to more task switches than others, Chiu and Egner (2017) demonstrated that the efficiency with which one switches between tasks (as measured by the task switch cost) is modulated by the degree to which the current item is associated to "the act of task switching".…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are consistent with a number of previous observations indicating that abstract goals or cognitive control functions can bind to contextual features in our environment, allowing for the recruitment of these functions upon contextual demand (Abrahamse et al, 2016). A more recent line of studies also extended this observation to the domain of "cognitive flexibility"the ability to quickly reconfigure our task sets to meet new goals (for a review, see Braem & Egner, 2018). For example, in a design where specific task items were associated to more task switches than others, Chiu and Egner (2017) demonstrated that the efficiency with which one switches between tasks (as measured by the task switch cost) is modulated by the degree to which the current item is associated to "the act of task switching".…”
Section: Discussionsupporting
confidence: 89%
“…More recently, Whitehead, Pfeuffer, and Egner (2020) showed this learning of stimulusflexibility associations can even occur after a single instance of experiencing a given stimulus under task repetition versus task switching conditions. The present study further extends this idea that cognitive flexibility can be regulated by the context, by showing context-specific cognitive flexibility under conditions where people do not just have to alternate between two or three tasks (Chiu and Egner, 2017;Whitehead et al, 2020), but between many new tasks, consistent with the idea of regulating a general updating threshold (Braem & Egner, 2018;Dreisbach & Fröber, 2018;Goschke, 2003;Goschke & Bolte, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In fact, the distinction between inhibitory control, working memory, and cognitive flexibility that Heyes relies on has also been partly challenged by the very authors who originally introduced this distinction (Friedman & Miyake 2017). Therefore, there is increasing evidence that executive functions are highly contextualized and "sticky" (Mayr & Bryck 2005), which we take as a strong hint that they might be grounded in associative learning (Abrahamse et al 2016;Braem & Egner 2018;Egner 2014). This makes executive functions ideally suited to develop through social communication and transfer to meet contextual and cultural demands (Hommel & Colzato 2017).…”
Section: Open Peer Commentarymentioning
confidence: 99%
“…Cognitive flexibility is suboptimal compared to behaviours that require less flexible processing (Kleinsorge & Rinkenauer, 2012;Shen & Chun, 2011) but can be improved by motivational factors, such as the prospect of reward for fast and accurate performance (Braem & Egner, 2018). When the prospect of reward is high, performance improves on flexible rule-based tasks (Etzel et al, 2016;Kleinsorge & Rinkenauer, 2012), suggesting that reward might optimise cognitive flexibility by tuning rule-based neural coding patterns.…”
Section: Introductionmentioning
confidence: 99%